2016
DOI: 10.1155/2016/3254857
|View full text |Cite
|
Sign up to set email alerts
|

The NPs Role of Assessing and Intervening with Older Adult Drivers

Abstract: As the silver tsunami continues, assessing and intervening with older adult drivers are becoming an essential aspect of the comprehensive geriatric exam. The current lack of time efficient clinical guidelines is a concern and barrier for NPs. The purpose of this study was to identify strategies currently used by NPs. The critical incident technique was used to obtain data from a convenience sample of NPs. A total of 89 incidents were collected. The perspective of the NP can provide important information for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Nurses can play a key role in screening and assessing older drivers. In their clinical practice, nurses and nurse practitioners see older adults who are still driving at least once a week, or more (Arms, 2016). Findings in Johnson (1998)’s study revealed that 38% of the nurse participants assessed their older clients for factors related to driving abilities.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nurses can play a key role in screening and assessing older drivers. In their clinical practice, nurses and nurse practitioners see older adults who are still driving at least once a week, or more (Arms, 2016). Findings in Johnson (1998)’s study revealed that 38% of the nurse participants assessed their older clients for factors related to driving abilities.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Arms (2016), NPs reported 6 major assessment categories and circumstances that trigger them to assess their older clients’ driving ability: (a) Assessing older drivers’ mental status, (b) identifying changes in physical status, (c) hearing concerns from family members, (d) evaluating medications, (e) retrieving driving information and (f) assessing drug and alcohol abuse. Some authors wrote articles related to this, to inform and raise nurses’ and NPs’ awareness about the age‐related physiological changes and health conditions affecting the driving performance of older adults (Brown, 2006; Johnson, 2003; Snyder, 2005; Towner & Yanochko‐Horsley, 2007; Wiese & Wolff, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations